EXTRASKELETAL OSTEOSARCOMA OF ANTERIOR ABDOMINAL WALL: A CASE REPORT AND REVIEW OF LITERATURE - Ali, Syed Salman; Zeeshan, Muhammad; Muhammad, Iqbal; Afzal, Saeed; Hashmi, Shoaib Naiyer; Hamdani, Syed Naeem Raza (Pakistan Armed Forces Medical Journal, 2020)
We report a case of an extremely rare soft tissue tumour, extraskeletal osteosarcoma in a 62 year old Pakistani male, who presented with a slowly growing painless mass of anterior abdominal wall and died within one year of diagnosis. The clinical, radiological and pathological features of this neoplasm will be discussed, along with a review of the literature.